THE USE OF SMALL GROUP VLOG VIDEO PROJECT TO INCREASE EFL STUDENTS CONFIDENCE IN ENGLISH PRESENTATION - Joko Prayudha.S (Akademi Komunitas Negeri Putra Sang Fajar Blitar, 2023)
Objective Learning by utilizing technology has become a good alternative in the implementation of teaching and learning activities. The development of learning applications and platforms has also emerged massively to support effective learning, so teachers must be able to maximize the use of this technology in order to develop students' communication and English skills by applying interesting learning methods. One of the learning methods that teachers can apply in integrating technology is by asking students to make a vlog video project about everyday life. Therefore, this study aims to determine the use of the video vlog project method to increase students' confidence in making presentations in English. Materials and Methods. This study uses a qualitative method and uses a descriptive approach to determine the uses and benefits of using the video vlog project method to increase students' confidence in making presentations in English. Data was obtained through collecting various literature related to the use of video vlogs in the form of journals, articles and books. In addition, interviews were also used as a data collection method to three English teachers to find out their perceptions of applying the video vlog method. Data were analyzed through three stages namely, data reduction, data display and conclusion. Results. Learning English using video vlog project method provides different teaching compared to ordinary learning. Students become more independent in making assignments related to the theme of the English language being studied. In addition, by utilizing video vlogs students can improve their speaking skills through video practice they make, learning becomes more creative, students are more actively involved in conversations and have positive results in carrying out presentations using English. It is hoped that teachers can use this method more optimally to continue to encourage and improve students' English proficiency. Conclusion. The use of technology in learning English has become a necessity that must be applied in learning, not only because of the demands of the times but because of the advantages offered by the technology to support the learning process. Thus, the use of vlog video in learning can be utilized by teachers in teaching English because they have advantages that can encourage students to increase their confidence when presenting in English.